STUDY OF PERFORMANCE INDICATORS OF TRANSPORT MACHINE-BUILDING AND RAILWAY INDUSTRY ENTERPRISES IN A PANDEMIC CONDITION COVID-19 (Transport systems and technologies, 2021)
The article analyzes the impact of the consequences of the quarantine measures introduction to counter the pandemic COVID-19 on the economy of Ukraine in general and the domestic transport machine-building sector in particular. It has been established that one of the most affected sectors of the economy is transport and mechanical engineering, in particular the railway transport sector. It is determined that at present a very relevant issue for the further development of domestic enterprises of transport machine-building and railway industry is the assessment of the impact of the COVID-19 pandemic on the activities and financial and economic performance of these enterprises. The financial and economic indicators of such domestic enterprises of transport machine-building and railway industry, such as JSC "Ukrzaliznytsia", PJSC "KVBZ", SE "UkrNDIV", LLC "LEMTRANS" and LLC "KERNEL-TRADE", TDV "Popasnyansky Car Repair Plant" are analyzed. It was determined that the most affected of the studied domestic enterprises under the conditions of quarantine measures were JSC "Ukrzaliznytsia", PJSC "KVBZ", TDV "Popasnyansky Car Repair Plant". The main reasons for the decrease in technical and economic indicators at domestic enterprises of transport machinebuilding and the railway industry are studied by the method of expert evaluation. According to the analysis of expert evaluation data, the most important reason for the deterioration of technical and economic indicators of enterprises is the lack of state support and incentives for the development of transport machine-building and the railway industry in the country (19.6%). Experts estimate the impact of the consequences of the introduction of quarantine measures to counter the COVID-19 pandemic at 8.1%. Measures are proposed to improve the technical and economic performance of the most affected domestic enterprises of the transport machine-building and railway industries in the context of the COVID-19 pandemic.
Keywords: domestic enterprise, railway industry, COVID -19 pandemic, resource-saving technologies, technical and economic indicators, transport machine-building.